The Evangelical Missionary Movement: The pure gospel, or can there be a bit of progress, enlightenment and colonialism? - Hille, Rolf (Vox Scripturae - Revista Teológica Internacional, 2017)
"In Evangelical theology, great emphasis is placed on preaching and teaching according to the Biblical word, and hence the term ""pure gospel"" plays a central role. Starting point for this article are observations in Ghana that make clear how, in the history of Evangelical mission, different contexts, not only the culture, have also profoundly shaped the life in the Christian communities in the sense of a comprehensive context. Both the British and the German colonial histories have left deep traces in Ghana and continue to shape the country today from the first grade in school all the way up to the public media. What is this really pure about, which the missionaries in the nineteenth and early twentieth centuries proclaimed and taught in Ghana, in the sense of the ideal (""the pure gospel""), in the sense of doctrinal biblical purity, and what are overlays and mingling with contextual specifications? In this context, it makes sense to look back at the tradition of the European history of philosophy, especially at idealism and Platonism, because there we already find the ambivalence of original purity in the sense of timeless ideas as well as the consideration of the real world as a more or less contaminated shape of the original ideas. In contrast to the Greek model, Biblical revelation is consistently historical. That is, God consciously and willingly manifests Himself in historical contexts by which He connects Himself to a very specific language, culture, and in the case of Israel, for example, to a specific country and a people chosen by Him. Analogous to this, the incarnation of God in Jesus Christ is likewise not an ideal concept of timeless, ideality detached from the world, but entering into the framework conditions of the created world. A problem of Western cultural history is now defined by the overlap between the Greek idealistic understanding of the purity of the idea, on the one hand, and the historical contingency of the revelation of God in the biblical texts (on the other hand). The purity of the gospel is characterized precisely by the fact that the message gets involved in the historical framework conditions and permeates them in such a way that they become the medium and form of the divine revelation in its accidental historical manifestation. In this horizon, another or new understanding of the purity of the biblical message comes into the discussion, namely, that which defined the Lutheran Reformation of the sixteenth century as an essential characteristic of the Church, namely, according to Article 7 of the Augsburg Confession: let the gospel be ""purely preached"".This purity has an entirely different goal than the idealistic understanding: the pure Gospel, in the sense of the Reformation rediscovery of the Gospel, is the message of the justification of the sinner by grace alone. In this sense, the gospel must be proclaimed purely, that the justification before God must not be supplemented by any addition and embellishment by man, but is solely and exclusively an act of divine grace. In terms of missionary history, however, and the assessment of today's global church, this means that the gospel can be drawn in a variety of contexts, and the key emphasis is that, with respect to soteriology, no human achievement can and must be provided by which man could acquire the salvation of God.